2013
DOI: 10.1088/0022-3727/46/20/202001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of correlation between 1/fnoise level and metal-to-insulator transition temperature in epitaxial La0.7Sr0.3MnO3thin films

Abstract: The relation between lattice deformation, dc electrical properties and 1/f noise at room temperature was investigated experimentally in two series of high epitaxial La 0.7 Sr 0.3 MnO 3 (LSMO) thin films of various thicknesses. The first series was deposited on SrTiO 3 (0 0 1) single crystal substrates by pulsed laser deposition and the second one on SrTiO 3-buffered Si (0 0 1) substrates by reactive-molecular-beam epitaxy. A clear correlation was found between 1/f noise level and the temperature of the metal-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The normalized Hooge parameters α H /n was then measured to be (4.2 ± 0.6) × 10 −31 m 3 at 300 K, which is about two times lower than the one measured in La 0.7 Sr 0.3 MnO 3 films of comparable thickness deposited on SrTiO 3 /Si with α H /n values of (9.8 ± 0.6) × 10 −31 m 3 at 300 K and only two times higher than the one measured in La 0.7 Sr 0.3 MnO 3 films of comparable thickness deposited on SrTiO 3 single crystal substrates with α H /n values of (2.47 ± 0.6) × 10 −31 m 3 . 39,58,59 In conclusion, we have shown the promise of epitaxial (100) p -oriented CaTiO 3 as a buffer layer for the integration of functional oxides having the perovskite structure with silicon. Specifically, we have grown high-quality epitaxial La 0.7 Sr 0.3 MnO 3 films on CaTiO 3 /Si.…”
Section: -mentioning
confidence: 79%
See 1 more Smart Citation
“…The normalized Hooge parameters α H /n was then measured to be (4.2 ± 0.6) × 10 −31 m 3 at 300 K, which is about two times lower than the one measured in La 0.7 Sr 0.3 MnO 3 films of comparable thickness deposited on SrTiO 3 /Si with α H /n values of (9.8 ± 0.6) × 10 −31 m 3 at 300 K and only two times higher than the one measured in La 0.7 Sr 0.3 MnO 3 films of comparable thickness deposited on SrTiO 3 single crystal substrates with α H /n values of (2.47 ± 0.6) × 10 −31 m 3 . 39,58,59 In conclusion, we have shown the promise of epitaxial (100) p -oriented CaTiO 3 as a buffer layer for the integration of functional oxides having the perovskite structure with silicon. Specifically, we have grown high-quality epitaxial La 0.7 Sr 0.3 MnO 3 films on CaTiO 3 /Si.…”
Section: -mentioning
confidence: 79%
“…Electrical low-frequency noise measurements were performed at 300 K in the same way as previously described. 39,58,59 The La 0.7 Sr 0.3 MnO 3 /CaTiO 3 /Si thin film was patterned by UV photolithography and argon ion etching to form a 50 µm wide and 150 µm long strip, which includes two gold pads for supplying the current and two gold pads at which the voltage was measured in a four-probe geometry. bias currents.…”
Section: -mentioning
confidence: 99%
“…3, inset) was estimated at temperature T mi = 412 K. The T C and T mi values coincide according to double-exchange theory explaining the ferromagnetic properties of manganites. The typical room temperature resistivity is about 1-2 mΩcm and maximal resistivity changes were observed at the temperatures around 330 K. The maximum of temperature coefficient of resistivity TCR = 2.7% K −1 was achieved at 321 K. Moreover, Méchin et al [5] found that the level of 1/f noise at room temperature decreases with increased value of T mi , therefore the presented LSMO thin film with T mi = 412 K seems to be a good candidate for room temperature application as sensor.…”
Section: Resultsmentioning
confidence: 95%
“…Thanks to the low 1/f noise the rare earth manganese oxides, such as La0.7Sr0.3MnO3 (LSMO), may then find important applications in magnetoresistive sensors [2]. In addition, LSMO exhibits a Curie temperature of about 350 K, which allows room temperature applications.…”
Section: Introductionmentioning
confidence: 99%